Surface Finishes for Ti-6Al-4V Alloy Produced by Direct Metal Laser Sintering - Longhitano,Guilherme Arthur (2015)
The implant’s surface is responsible for direct interaction with the human body. For cases where osseointegration must be favored and the risk of bacteria proliferation is lower, rough surfaces are more suitable, while for implants where the risks are higher, a reduced surface roughness is required. This study aimed to analyze and produce different surface finishes on samples of Ti-6Al-4V alloy produced by additive manufacturing technique of Direct Metal Laser Sintering (DMLS). Surfaces of the samples were analyzed in the as-built condition, after blasting, after chemical etching, after electropolishing and two different combinations of these methods. The surfaces were studied using the technique of scanning electron microscopy, and surface roughness and mass measurements. The lower roughness value was obtained after a combination of blasting and chemical etching. Blasting results in a surface with uniform roughness while chemical etching cleans the surface and reduces its roughness.